Multiple sulfur isotopes and the evolution of the atmosphere - Farquhar, J.; Wing, B. A. (Earth and Planetary Science Letters, 2003)
Interest in multiple sulfur isotope analyses has been fueled by recent reports of mass-independent sulfur isotope signatures in the geologic record. A non-zero multiple isotopic signature of sulfur (Delta(33)S and Delta(36)S) is produced primarily through photochemical reactions, and it is an almost perfect tracer of the source of sulfur. Once the signature is passed on to a given sulfur reservoir, it will be preserved unless there is addition of sulfur with a different Delta(33)S or Delta(36)S. In the geological record, this signature has been used to study the evolution of the Earth's atmosphere and to trace movement of sulfur through geological systems early in Earth's history. Recently, small but significant mass-independent sigriatures have been reported for some younger samples, raising the possibility of additional applications of multiple isotope studies. The purpose of this review is to introduce and discuss the implications of multiple isotope studies and to focus attention on these anomalous, but not uncommon isotopic signatures. (C) 2003 Elsevier Science B.V. All rights reserved.
708vdTimes Cited:280Cited References Count:56